The Effect of Using Dual Situated Learning Model (DSLM) to Teach Chemistry in the Development of Conceptual Comprehension of Secondary School Female Students - Hamdi, Ebtisam Ali (Journal of Curriculum and Teaching Methodology, 2025)
The current study aimed to detect the effect of using a dual situated learning model (DSLM) to teach chemistry in the development of conceptual comprehension of secondary school female students. In order to achieve the objective of the study, the experimental method was based on semi-experimental design. The study sample consisted of (70) second grade secondary school female students in Sabia province. The sample was randomly divided into two groups. The experimental group consisted of (35) students who studied using a dual situated learning model (DSLM), and the control group consisted of (35) students group who studied using the conventional method. The results of the study were statistically significant at (α ≤ 0.05) between the mean scores of the experimental and control groups in the post-application of the conceptual comprehension test in favor of the experimental group. In light of these results, the study recommended that use of the dual situated learning model (DSLM) in teaching and learning chemistry for secondary school students. The study also recommended holding training courses and programs, and workshops to train chemistry teachers on the use and application of a dual situated learning model (DSLM) during planning and implementation of lessons.